2012
DOI: 10.1039/c2cs35140d
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric OH and HO2 radicals: field measurements and model comparisons

Abstract: The hydroxyl radical, OH, initiates the removal of the majority of trace gases in the atmosphere, and together with the closely coupled species, the hydroperoxy radical, HO(2), is intimately involved in the oxidation chemistry of the atmosphere. This critical review discusses field measurements of local concentrations of OH and HO(2) radicals in the troposphere, and in particular the comparisons that have been made with numerical model calculations containing a detailed chemical mechanism. The level of agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
432
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 491 publications
(465 citation statements)
references
References 315 publications
(617 reference statements)
30
432
2
1
Order By: Relevance
“…This box modelling study is consistent with previous studies (Kanaya et al, 2002(Kanaya et al, , 2007Bloss et al, 2005a;Sommariva et al, 2007;Whalley et al, 2010;Mahajan et al, 2010a;Stone et al, 2012) in that it implies that halogen chemistry is likely to increase the OH concentration of the marine boundary layer (and potentially other regions of the troposphere) as it enhances the HO 2 to OH conversion through the production of HOBr and HOI. We now look at the impact of halogen chemistry on the concentrations of OH and HO 2 at the Cape Verde Atmospheric Observatory within the framework of a global atmospheric chemistry model.…”
Section: Constrained Box Modelsupporting
confidence: 79%
“…This box modelling study is consistent with previous studies (Kanaya et al, 2002(Kanaya et al, , 2007Bloss et al, 2005a;Sommariva et al, 2007;Whalley et al, 2010;Mahajan et al, 2010a;Stone et al, 2012) in that it implies that halogen chemistry is likely to increase the OH concentration of the marine boundary layer (and potentially other regions of the troposphere) as it enhances the HO 2 to OH conversion through the production of HOBr and HOI. We now look at the impact of halogen chemistry on the concentrations of OH and HO 2 at the Cape Verde Atmospheric Observatory within the framework of a global atmospheric chemistry model.…”
Section: Constrained Box Modelsupporting
confidence: 79%
“…In general, the observed OH levels for this study are comparable with previously reported OH levels from other moderately polluted environments. 39 The observed daytime H 2 SO 4 maximum was ∼7 × 10 6 molecules cm −3 . This is much lower than the reported values (∼2 × 10 7 molecules cm −3 ) for airborne observations over the boundary layer of Northeastern U.S. and the Ohio Valley region during NEAQS-2004.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…For example, Bigi and Harrison (2010) report a steady increase in ozone between 1996-2008 in North Kensington; an urban background site in London. 20 To implement efficient reduction strategies for ozone, a detailed understanding of the factors controlling free radicals is critical since the reaction of HO2 and RO2 radicals with NO, forming NO2, followed by the subsequent photolysis of NO2 represents the only net formation pathway to tropospheric ozone: Measurements of radicals have been made at various urban and sub-urban locations worldwide, both during the summer and winter (Stone et al (2012) and references therein). Observations of OH and HO2 in the urban atmosphere have primarily been 5 made using fluorescence assay by gas expansion (FAGE), and comparisons with predicted radical concentrations using chemistry box models constrained with co-located radical precursor measurements have revealed varying levels of success in replicating observations.…”
Section: Introductionmentioning
confidence: 99%